A novel fluorescent off–on probe for the sensitive and selective detection of fluoride ions. Issue 55 (10th October 2019) - Li, Lihong; Zhang, Min; Chang, Kaijing; Kang, Yu; Ren, Guodong; Hou, Xiaoyu; Liu, Wen; Wang, Haojiang; Wang, Bin; Diao, Haipeng
Abstract : A sensitive and selective fluorescent off–on probe is developed for fluoride ion detection, and its applicability has been demonstrated by determining fluoride ions in real-water samples and toothpaste samples. Abstract : A highly sensitive and selective fluorescent probe for fluoride ions has been developed by incorporating the dimethylphosphinothionyl group as a recognition moiety into the fluorophore of coumarin. The detection mechanism is based on the fluoride ion-triggered cleavage of the dimethylphosphinothionyl group, followed by the release of coumarin, which leads to a large fluorescence enhancement at 455 nm ( λ ex = 385 nm). Under the optimized conditions, the fluorescence enhancement of the probe is directly proportional to the concentration of fluoride ions in the range of 0–30 μM with a detection limit of 0.29 μM, which is much lower than the maximum content of fluoride ions guided by WHO. Notably, satisfying results have been obtained by utilizing the probe to determine fluoride ions in real-water samples and commercially available toothpaste samples. The proposed probe is rather simple and may be useful in the detection of fluoride ions in more real samples.